1997
DOI: 10.2307/1592342
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Novel Infectious Bursal Disease Virus Immune Complex Vaccine in Broiler Chickens

Abstract: Two experiments were conducted to test the efficacy of a novel infectious bursal disease virus (IBDV) vaccine in broiler chickens with maternal IBDV immunity. The IBDV vaccine was formulated by mixing IBDV strain 2512 with bursal disease antibodies (BDA) to produce the IBDV-BDA complex vaccine. In Expt. I, 1-day-old Cobb x Cobb broiler chickens were vaccinated subcutaneously with either IBDV-BDA or commercial live intermediate IBDV vaccine (vaccine A) or were left unvaccinated. In Expt. 2, the vaccine A group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 17 publications
1
30
0
6
Order By: Relevance
“…The same vaccine when administered subcutaneously to one day old chicks resulted in a detectable antibody response (24,43). In most studies, it has been clearly indicated that chickens vaccinated as embryos acquire higher antibody levels that are sustained at high levels over the normal broiler's rearing period.…”
Section: Discussionmentioning
confidence: 99%
“…The same vaccine when administered subcutaneously to one day old chicks resulted in a detectable antibody response (24,43). In most studies, it has been clearly indicated that chickens vaccinated as embryos acquire higher antibody levels that are sustained at high levels over the normal broiler's rearing period.…”
Section: Discussionmentioning
confidence: 99%
“…The immune-complex vaccine, on the other hand, is innovative compared with conventional live vaccines because the vaccine virus is coated with anti-IBD antibodies, and when administered to one-day-old chicks, its pathological effects are delayed up to one week, during which the level of maternal antibodies is greatly reduced (Haddad et al, 1997;Jeurissen et al, 1998).…”
Section: Infectious Bursal Disease: Pathogenicity and Immunogenicity mentioning
confidence: 99%
“…Despite the BF lesions caused by immune-complex vaccines, some researchers stated that the vaccine antibodies may reduce the pathogenicity of the virus, resulting in less severe depletion of B lymphocytes when compared with live vaccines with the same virus strain (Haddad et al, 1997;Jeurissen et al, 1998). On the other hand, Moraes et al (2004) recommends caution when using live vaccines that may cause BF lesions, as the recovery of bursal follicles may be only partial.…”
Section: Infectious Bursal Disease: Pathogenicity and Immunogenicity mentioning
confidence: 99%
See 1 more Smart Citation
“…This immune complex vaccine is developed by mixing live intermediate plus infectious bursal disease virus (IBDV) with hyperimmune IBDV chicken serum (IBDV-Icx vaccine) [38].…”
Section: Immune Complex Vaccinementioning
confidence: 99%